Implementasi Kebijakan Pengelolaan Keuangan Dana Desa di Kabupaten Bone Bolango - Elnino M.Husein Mohi; Rukiah Nggilu; I Kadek Satria Arsana (Al-Mada: Jurnal Agama, Sosial, dan Budaya, 2022)
This study aims to determine and analyze the implementation of financial management policies in Bone Bolango Regency. The population is determined based on purposive sampling. This study uses a qualitative descriptive method, starting with the collection process in the form of primary data originating from the local government, both the district government, in this case the Village Empowerment Service (BPMD) and the village government in Bone Bolango Regency. Techniques of data analysis were obtained through data collection, data presentation and sampling of the inhibiting factors of village fund management policies, namely communication factors, resources, placement, employees. Although the Village Fund is experiencing socio-economic problems in meeting needs, this is due to the COVID-19 pandemic since the end of 2019 until now 2022, so that infrastructure support programs and activities cannot be implemented yet, they are still focused on handling COVID-19 and food security. One of the government's policies in implementing the village financial policy, which accelerates the economic growth of rural communities, has an impact on reducing poverty, health and quality of life for rural communities, as well as developing local products and preserving nature in rural areas of Bone Bolango Regency.